ChemInform Abstract: Pyridinoacridine Alkaloids of Marine Origin: NMR and MS Spectral Data, Synthesis, Biosynthesis and Biological Activity. Issue 12 (March 2016) - Sandjo, Louis P.; Kuete, Victor; Biavatti, Maique W.
Abstract: Review: [101 refs.